The effects of compost produced from rice oryza satuva straw and sugarcane sacccharum officinarum trash on the growth of pechay Brassica rapa. - Brizuela, Karlyn G.
This study was designed to determine the effects of the application of compost produced fron Oryza sativa and sugarcane Saccharum officinarum trash on the growth of pechay Brassica rapa. Experiments were carried out in a residential lot in Brgy. Punta Taytay, Bacolod City, Negros Occidnetal. Four set-ups were made with three replicates each. Each set-up corresponded to one compost treatment: treatment (A) was the rice straw compost, treatment (B) was the sugarcane trash compost, treatment (C) was the combination of rice straw and sugarcane trash compost, and treatment (D) served as the control in which no compost was added. The results of the statistical tests showed that there was a significant increase in the growth of pechay plants treated with the three different types of composts as compared to the pechay plants treated with the control. Among all the treatment, pecahy plants treated with the combination of rice straw and sugarcane trash compost showed the highest growth yield in terms of the mean plant height (19.61 cm), mean fresh weight (44.95 g), and mean number of leaves per plant (8.99) at the time of harvest. Results also showed that there was no significant difference in the mean fresh weight and mean number of leaves per plant at the time of harvest in pechay plants treated with the rice straw compost and the sugarcane trash compost.